NILAI PENDIDIKAN KARAKTER BERBASIS KEARIFAN LOKAL DALAM FILM INDIE BANYUMAS - Teguh Trianton (Khazanah Pendidikan, 2013)
Film is entertainment for people who are able to penetrate the social class boundaries. The ability to reach various segments of the film class, film making has the potential to affect masyarakt audience. Strategic value of the film not only serves as entertainment, the film has the potential as a medium of education, which can effectively communicate educational messages, and even be able to influence a person's behavior. This is the one of the spirit for student filmmakers in Purbalingga, Banyumas, Cilacap and Banjarnegara continues to be creative by producing indie films. Film is the medium for the message menyampaiakn, storytelling and expression. As with any work of literature (novels, short stories, drama, theater), in the film there is also a story, the scene, dialogue, scene, conflict, character, character, and setting. One of the benefits is being able to visualize movie various human characters so that it can easily intervene or influence the minds of the audience. This is where the potential effectiveness of the film in instilling moral values as part of the educational aspect of the nation's character.